Evaluation of the facial soft tissue thickness in a Brazilian in vivo population "facial soft tissue thickness in Brazilians" - Marília Moura Freitas da-Silva; Gabriela Granja Porto; Antônio Azoubel Antunes; Evelyne Pessoa Soriano; Marcus Vitor Diniz de-Carvalho; Rafael de Sousa Carvalho Saboia (Revista Brasileira de Cirurgia Plástica)
Introduction: Nowadays there is a huge demand for individual identification in both civil and criminal justice fields. There are several ways to identify individuals, depending on whether he is alive or dead (cadaver or skeleton). This research aimed to create a database for facial soft tissue thickness in living individuals of a specific Brazilian population, according to age, sex and body mass index. Methods: Measurements of facial soft tissues thickness were done in 101 patients (62 men and 39 women, aged 18 to 106 years). CT scans were performed taking into account 20 craniometric points previously selected. The soft tissue thickness in these points were initially found and compared with age, sex and nutritional status, and with another populations data worldwide. Results: According about sex was no significant difierence in points: nasion, rhinion, midphiltrum, supradentale and lateral orbit. Distances with significant difference for both sexes between the diferent populations were: supradentale; infradentale; supramentale; lateral orbit; zygomatic arch and occlusal line. Some anthropometric points showed significant differences between sex, age groups and nutritional status. Between sexes, men had greater means. Among age groups, there was also significant differences in some distances. In relation to nutritional status, the distances were lower among normal weight and higher among the obese. Conclusion: When considering various populations, soft tissue thickness had significant differences in many craniometric points highlighting how distinct they might be.